2019
DOI: 10.1016/j.jtcvs.2019.04.068
|View full text |Cite
|
Sign up to set email alerts
|

Invasive mediastinal staging for resected non–small cell lung cancer in a population-based cohort

Abstract: Objectives: Invasive mediastinal nodal staging is recommended before curativeintent resection in patients with non-small cell lung cancer deemed at risk for mediastinal lymph node involvement. We evaluated the use and survival effect of preoperative invasive mediastinal nodal staging in a population-based nonsmall cell lung cancer cohort. Methods:We analyzed all curative-intent resections for non-small cell lung cancer from 2009 to 2018 in 11 hospitals in 4 contiguous Dartmouth Hospital Referral Regions, compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 29 publications
0
29
1
Order By: Relevance
“…[4][5][6] Recently, one cohort study reported that proper preoperative staging was associated with survival benefits in patients with non-small cell lung cancer (NSCLC). 7 The superiority of EBUS-TBNA over radiological imaging, such as computed tomography (CT) and positron emission tomography-CT (PET-CT), has been attributed to its higher diagnostic accuracy rate (DAR). 4 Two meta-analyses reported a cumulative sensitivity and specificity of 88%-93% and 100%, respectively, for EBUS-TBNA in NSCLC staging; however, targeted LNs had a short axis diameter of at least 1 cm on CT in the majority of the included studies.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Recently, one cohort study reported that proper preoperative staging was associated with survival benefits in patients with non-small cell lung cancer (NSCLC). 7 The superiority of EBUS-TBNA over radiological imaging, such as computed tomography (CT) and positron emission tomography-CT (PET-CT), has been attributed to its higher diagnostic accuracy rate (DAR). 4 Two meta-analyses reported a cumulative sensitivity and specificity of 88%-93% and 100%, respectively, for EBUS-TBNA in NSCLC staging; however, targeted LNs had a short axis diameter of at least 1 cm on CT in the majority of the included studies.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate staging has been reported to reduce the number of futile operations, and improve the quality of surgery and survival. 15,16 Standardized low-technology exercise testing integrated in our routine risk assessment seemed to provide an excellent estimate of the physiological capacity of these patients. 3 Third, the overall high rate of minimally invasive approaches, anatomic lung resections, R0 resections, and formal lymphadenectomies, together with a low rate of major morbidity and 90-day mortality reflects the quality of the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…3 Recent studies show substantial improvements with rates of mediastinoscopy without nodal tissue down to 7% to 17%. 4,5 Similar concerns apply to EBUS. EBUS is known to have diagnostic yields that are low (37%-54%) and variable across centers.…”
mentioning
confidence: 95%